PERAN KEPEMIMPINAN DALAM PERSPEKTIF MAJAJEMEN MUTU TERPADU (MMT) STRATEGI INOVATIF UNTUK MENINGKATKAN MUTU PENDIDIKAN: Manajemen Mutu Terpadu, Kepemimpinan, Mutu Pendidikan, Evaluasi Sekolah - MAHLAN, HAMINI; Aryna Tambunan, Audi; Dahyanti, Dahyanti; Azainil, Azainil (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2025)
Total Quality Management (TQM) plays a crucial role in improving educational quality, with leadership being a key success factor. This study analyzes the relationship between leadership styles and the effectiveness of TQM implementation in five senior high schools in Tenggarong. Using a quantitative descriptive-correlational approach, data were collected through Likert-scale structured interviews with 5 school principals, 3 teachers, and 2 administrative staff. The purpose of this study is to analyze the relationship between leadership style and the effectiveness of MMT implementation in improving the quality of education. Aims to clarify the core concepts underlying the analysis of the role of leadership in the implementation of Integrated Quality Management (IQM) in the school environment. This discussion includes leadership theory, quality management theory, and the relationship between the two in the world of education. In the context of education, leadership has a central role in forming an environment that supports the learning process and improving the quality of education. The findings reveal that transformational leadership significantly contributes to successful TQM implementation, particularly in enhancing teacher involvement, managerial effectiveness, and quality evaluation. In contrast, schools with bureaucratic leadership face greater challenges in adopting TQM policies. Key supporting factors include teacher participation and technology utilization, while major obstacles include limited resources and resistance to change. In conclusion, innovative and participatory leadership is essential for effective TQM implementation. This study provides insights for developing more structured and sustainable educational quality management policies